Comparison of coercivity and squareness in hot-deformed and sintered magnets produced from a Nd-Fe-B-Cu-Ga alloy. (February 2019) - Xu, X.D.; Sepehri-Amin, H.; Sasaki, T.T.; Soderžnik, M.; Tang, X.; Ohkubo, T.; Hono, K.
Abstract: We have fabricated a hot-deformed magnet from the Fe77.1 Nd11.6 Pr3.7 B5.1 Cu0.1 Co1.0 Al0.9 Ga0.5 alloy composition that was developed for exchange-decoupled sintered magnet. The hot-deformed magnet showed a higher coercivity, μ 0 H c = 1.93 T, and better squareness, H k90 /H c = 0.96, compared to those of the sintered magnet, μ 0 H c = 1.48 T and H k90 /H c = 0.65. Microstructural analyses revealed the higher coercivity in the hot-deformed magnet originates from a larger contribution from the anisotropy term in the Kronmüller formula owing to fine grains, while the better squareness is primarily due to the exchange coupling of the Nd2 Fe14 B grains through ferromagnetic grain boundary phase, as suggested by atom probe tomography and magneto-optical Kerr effect microscopy. Graphical abstract: